1973
DOI: 10.1128/aem.25.2.305-308.1973
|View full text |Cite
|
Sign up to set email alerts
|

Lysogeny in Lactic Streptococci Producing and Not Producing Nisin

Abstract: Eighty-seven strains of lactic streptococci (46 of Streptococcus lactis, 24 of S. diacetilactis, and 17 of S. cremoris) were tested for lysogeny; 12 S. lactis strains produced nisin. Lysogeny was found in five S. lactis strains (two of them were nisin producers) and in two S. diacetilactis strains. Four S. lactis and two S. diacetilactis lysogens liberated phages both spontaneously and after ultraviolet treatment, and one S. lactis strain liberated phages spontaneously only. No lysogens were found among the S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1974
1974
1994
1994

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 1 publication
1
20
0
Order By: Relevance
“…As early as 1949, Reiter (22) demonstrated that some strains of lactic streptococci were lysogenic. Subsequent reports (6,12,14,16) have confirmed the existence of lysogenic lactic streptococci. Park and McKay (19) recently reported that nine of twelve commercial dairy starter cultures used in the United States contained phage-harboring strains.…”
mentioning
confidence: 87%
“…As early as 1949, Reiter (22) demonstrated that some strains of lactic streptococci were lysogenic. Subsequent reports (6,12,14,16) have confirmed the existence of lysogenic lactic streptococci. Park and McKay (19) recently reported that nine of twelve commercial dairy starter cultures used in the United States contained phage-harboring strains.…”
mentioning
confidence: 87%
“…Reports in the literature reveal that more than 300 strains of L, lactis ssp. lactis and cremoris have been found to be lysogens [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The general conclusion that can be reached from these studies is that lysogeny is widespread in cheese starter strains and that multilysogenic strains also occur [15,21,22].…”
Section: Lactococcusmentioning
confidence: 99%
“…Latent periods for the induction of temperate phages are usually between 1 and 4 h [8,9,19,26]. Shorter latent periods have been observed when the phage infects its indicator strain [8]. Lack of data on the molecular biology of the life cycle is one of the major deficiencies in our knowledge of temperate phage infecting lactic acid bacteria.…”
Section: Temperate Phage Life Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…Some lysogenic strains have also been found in groups G (3) and H (11). Very recently lysogeny was demonstrated in strains of group N streptococci designated as Streptococcus lactis (7, 9) and S. diacetilactis (7), although lysogeny was not found in S. cremoris (7). Lysogeny in the S. cremoris strains of group N lactic streptococci, used as starters in cheesemaking, has been suspected for some years (4,5,12,14), but in no case has the presumed lysogeny been rigorously demonstrated.…”
mentioning
confidence: 99%